Energy management for a series hybrid electric vehicle (HEV) - Mohamad Kamal Hilmi, Mohd Rafi (2012)
The studies for hybrid electrical vehicle (HEV) have attracted considerable attention because of the necessity of developing alternative methods to generate energy for vehicles due to limited fuel based energy, global warming and exhaust emission limits in the last century. HEV incorporates internal composition engine, electric machines and power electronic equipments. In this study, overview of HEVs with a focus on hybrid configurations and energy management strategies are presented. This project is to be carried out by perform a demonstration of small scaled hardware that will used remote control (RC) parts as components to this project. First phase of the project will be focusing on software that will monitoring the speed of DC motor and perform a close loop that will estimate the energy requirement in certain condition. While the second phase of the project will be focusing on hardware development integrating with energy management software. The ratings of the battery and engine and the power output that will be delivered by each source under the expected condition will be considered in this paper. In this paper, the software and hardware that will be used and integrated will mention. An in house series hybrid electric vehicle will develop and in other word this paper presents the small scale of Series Hybrid Electric Vehicle (SHEV).